A Jurisdictional Review of Hearing Loss Screening Practices for School Children in Remote Communities - Ke Law-Gallagher, Xin (SciWise, 2025)
This study evaluates the feasibility of implementing a hearing loss screening program in Nunavut schools and was presented at the 2025 McMaster University Child Health Research Conference.